Paper Waste as a Creative Platform for Elementary School Students in Sumberejo Village - Fikriya Labiba; Najwa Fila Shofa; Wahyu Wulandari; Erma Erviana (Universitas Palangka Raya, 2024)
Creativity is an individual's ability to create novelty in the form of ideas or tangible works. In order to enhance creativity among students, community service has initiated activities that utilize paper waste to foster creativity, such as handicrafts. The primary objective is to reduce paper waste accumulation while fostering creativity among 5th and 6th-grade students. The method used involves hands-on activities where students transform sheets of newspaper into pencil holders, teaching them the value of recycling and creative problem-solving. The results show that students demonstrated both cognitive creativity traits, such as originality and flexibility, and non-cognitive traits, like curiosity and motivation. The program not only addresses waste management issues but also helps students develop practical skills, raising environmental awareness and instilling values of sustainability. Through this initiative, the creative potential of students is enhanced while contributing to environmental preservation.